1992
DOI: 10.1002/tcm.1770120102
|View full text |Cite
|
Sign up to set email alerts
|

Neural tube and other developmental anomalies in the guinea pig following maternal hyperthermia during early neural tube development

Abstract: Guinea pigs were exposed to hyperthermia for 1 hr once or twice on day 11, 12, 13, or 14 (E11-E14) of pregnancy. The mean rectal temperatures were elevated by 3.4 degrees C-4.0 degrees C. This treatment resulted in a marked elevation of rates of resorption and developmental defects in embryos examined at day E23. The defects observed were those affecting the neural tube (NTD) (exencephaly, encephaloceles, and microphthalmia), kyphosis/scoliosis, branchial arch defects, and pericardial edema. Embryos with NTD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…8. Previous reports have documented anophthalmos as a heritable trait, 22 and as occurring after pyrexia during gestation, 23 but no such previous history was apparent for the animal affected in this study. While blindness appears not to be an obstacle to a happy healthy guinea pig life, the ocular surface irritation occasioned by trichiasis as seen in Texel cavies such as those in Fig.…”
Section: Discussioncontrasting
confidence: 63%
“…8. Previous reports have documented anophthalmos as a heritable trait, 22 and as occurring after pyrexia during gestation, 23 but no such previous history was apparent for the animal affected in this study. While blindness appears not to be an obstacle to a happy healthy guinea pig life, the ocular surface irritation occasioned by trichiasis as seen in Texel cavies such as those in Fig.…”
Section: Discussioncontrasting
confidence: 63%
“…Experimental studies in mice and guinea pigs have revealed that immersion in a hot bath or isolation in a thermal box during early pregnancy increases the risk of many birth defects, including NTDs, kyphosis or scoliosis, branchial arch defects, and pericardial edema (Cawdell-Smith et al, 1992;Shiota, 1988). In general, the risk of birth defects increases if the body temperature increases 2.0 to 2.58C or more above the normal resting temperature for the experimental animals (Edwards et al, 1995); this is equivalent to a temperature of 39.0 to 39.58C (102.2 to 103.18F) in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of a teratogenic effect of fever was first postulated by researchers conducting ecologic studies of influenza and birth defects (Janerich, 1971;MacMahon & Yen, 1971). Stronger evidence of an association between maternal exposure to hyperthermia and an increased occurrence of birth defects was subsequently provided by animal studies (Cawdell-Smith, Upfold, Edwards, & Smith, 1992;Edwards, Shiota, Smith, & Walsh, 1995;Finnell, Moon, Abbott, Golden, & Chernoff, 1986) and epidemiologic studies of fever and neural tube defects (NTDs) (Kurppa, Holmberg, Kuosma, Aro, & Saxen, 1991;Li et al, 2007;Lynberg, Khoury, Lu, & Cocian, 1994;Medveczky, Puho', & Czeizel, 2004;Milunsky et al, 1992;Moretti, Benjamin, Fried, & Koren, 2005;Shaw, Todoroff, Velie, & Lammer, 1998;Shaw et al, 2002;Suarez, Felkner, & Hendricks, 2004;Yin et al, 2011;Zhang and Cai, 1993). A recent systematic review by Dreier, Andersen, and Berg-Beckhoff (2014) noted that the literature supports an association between maternal fever and an increased risk of birth defects, with the strongest associations for NTDs, oral clefts and cardiac defects.…”
Section: Introductionmentioning
confidence: 99%